Green Synthesis of Silver Nanoparticles Using Leaves of Chromolaena odorata and its Antioxidant Activity: Green Synthesis of Silver Nanoparticles using C. odorata - Siti Ernieyanti Hashim; Angelle Patrick John (Journal of Tropical Life Science, 2023)
Harmful chemical waste is a serious problem being faced during the synthesis of nanoparticles due to the usage of hazardous chemicals. Synthesis of silver nanoparticles using aqueous extract of the leaves of C. odorata is cheap and environmentally friendly. This study reports the synthesis of silver nanoparticles (AgNPs) using C. odorata aqueous extract as reducing agent. The leaves of C. odorata was extracted by using cold maceration technique. The phytochemicals screening of leaves was done and positive results was showed for the presence of flavonoids, tannins, saponins, and phenolics in the leaves extract of C. odorata. The synthesized C. odorata extract mediated AgNPs was characterized using several techniques including UV-Visible spectroscopy and Field Emission Scanning Electron Microscopy (FESEM). The reduction of pure Ag (I) ions to Ag (0) was monitored using UV-Vis every one hour after 24 hours up to 28 hours and it showed an absorption band at 430-450 nm. Field emission scanning electron microscopy (FESEM) was utilized to determine its particle size and the average particle size obtained was 27.3 nm. The silver nanoparticles (AgNPs) produced by using C. odorata leaves aqueous extract was determined for its antioxidant activity by using DPPH free radical scavenging assay. The IC50 value obtained was 277.29 mg/ml. Based on the results obtained, it indicates that the silver nanoparticles (AgNPs) produced using C. odorata leaves aqueous extract possessed antioxidant activity that can scavenge free radicals.